DETERMINANTS OF RURAL AND URBAN LAND AND BUILDING TAX COMPLIANCE: THE MODERATING ROLE OF TAX SOCIALIZATION IN CIBIRU DISTRICT - Leni Lusiawati; Purnamasari , Dyah (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyse the influence of Tax Knowledge, Tax Service Quality, and Taxpayer Awareness on Rural and Urban Land and Building Tax Compliance with Tax Socialisation as a moderating variable in Cibiru District, Bandung City. The novelty of this study lies in the integration of the role of Tax Socialisation as a moderating variable, which has not been widely studied in the context of Rural and Urban Land and Building Tax, thus contributing to the understanding of the mechanism of how the interaction between taxpayers' internal factors and government intervention affects tax compliance. This study uses primary data collected through a quantitative approach employing proportionate stratified random sampling, with 389 questionnaires distributed to Rural and Urban Land and Building Tax in Cibiru District. Data analysis was conducted using Moderated Regression Analysis (MRA) in SPSS version 29. The results show that Tax Service Quality and Taxpayer Awareness have a significant effect on taxpayer compliance. Tax Socialisation moderates the effects of Tax Knowledge and Tax Service Quality on compliance, whereas it does not moderate the effect of Taxpayer Awareness on compliance. These findings provide empirical and practical contributions to the development of strategies to improve Rural and Urban Land and Building Tax compliance through improving the socialisation and quality of tax services.